1998
DOI: 10.1088/0953-2048/11/2/009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of boron-containing dopants on the formation of superconducting phase in the system Bi(Pb)-Sr-Ca-Cu-O

Abstract: The effective dopants of , which formed phases compatible with the basic superconductor and did not cause the superconducting properties of Bi-2223 to deteriorate, was studied. It was found that the addition of 10 mol% of led to a reduction of the induction period and to an increase of the Bi-2223 phase content. It was shown that the surplus increased the amount of liquid in the system and thus accelerated the formation of Bi-2223 phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 11 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…If theoretical density is assumed to be equal to 6.3 g/cm 3 , this indicates that the pellets do have 29-40% porosity. It was reported that addition of 20-30% Ag increases the material density, improves the grain boundaries and increases pinning strength [24].…”
Section: System IImentioning
confidence: 99%
“…If theoretical density is assumed to be equal to 6.3 g/cm 3 , this indicates that the pellets do have 29-40% porosity. It was reported that addition of 20-30% Ag increases the material density, improves the grain boundaries and increases pinning strength [24].…”
Section: System IImentioning
confidence: 99%
“…224,225,229,230 Introduction of submicrometre-sized SrZrO 3 particles into (Bi,Pb)2223 ceramics causes an increase in the current flowing within grains. 176 At the same time, the Ca 2 B 2 O 5 additive has little effect on J c , 218 while the addition of BiSr 1.5 Ca 0.5 Al 2 O z and vanadium-containing oxide (see Table 2) leads to reduction of J c , especially at nonzero magnetic fields. 219,225 Considerable enhancement of magnetic flux pinning was observed upon introduction of MgO in the form of micro-and nanoparticles or nanowhiskers into the (Bi,Pb)2223 ceramics and silver-sheathed tapes.…”
Section: Microcomposites Based On Phases Of the Bi ± (Pb) ± Sr ± Ca ±...mentioning
confidence: 99%
“…Hence, researchers have done substantial work to improve their T C . At present, the most commonly used method is chemical doping, such as doping Cs [ 17 ], Al [ 18 ], SnO 2 [ 19 ], ZrO 2 [ 20 ], Ca 2 B 2 O 5 [ 21 ], and others in BSCCO. However, most of the dopants are unstable at high temperatures and will react with superconductors; the results are not ideal.…”
Section: Introductionmentioning
confidence: 99%